2019
DOI: 10.14710/politika.12.1.2021.1-10
|View full text |Cite
|
Sign up to set email alerts
|

Partisipasi Politik dan Pemilih Muda: Konteks Pilgub Jateng 2018 dan Pilkada 2019 di Kabupaten Temanggung

Abstract: Tulisan ini mengkaji kecenderungan partisipasi pemilih pemula di Jawa Tengah menjelang Pemilihan Gubernur 2018, dengan lokasi penelitian di Kabupaten Temanggung. Sebagaimana diketahui, partisipasi politik dalam pemilu sering dikaitkan dengan persentase kehadiran pemilih dalam tempat pemungutan suara (TPS). Tingkat partisipasi politik ini seringkali dihubungkan dengan legitimasi hasil pemilu, yakni seberapa besar dukungan suara yang didapat oleh pemenang pemilu, dimana makin tinggi tingkat partisipasi maka hasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…One of the main issues that occur in this process of political democracy is the practice of money politics. According to the findings of Kartodirdjo and Kana (Fitriyah, 2015) the practice of money politics in the implementation of Pilkades is not something new. In village life where election practices have been going on for a long time, distributing something to voters is part of the responsibility of "giving" a candidate for village head.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main issues that occur in this process of political democracy is the practice of money politics. According to the findings of Kartodirdjo and Kana (Fitriyah, 2015) the practice of money politics in the implementation of Pilkades is not something new. In village life where election practices have been going on for a long time, distributing something to voters is part of the responsibility of "giving" a candidate for village head.…”
Section: Introductionmentioning
confidence: 99%
“…Votes buying in general elections is a common practice that can be found in Third World countries. Many studies have shown that this practice occurs in Mexico (Vilalta 2010), Thailand (Bowie 2008;Callahan 2005;Callahan and McCargo 1996), Kenya (Kramon 2016), Nicaragua (Gonzalez-Ocantos et al 2012), Malaysia (Teh 2002;Weiss 2014), Argentina (Brusco, Nazareno, and Stokes 2004), Indonesia (Aspinall et al 2017;Aspinall and Mada 2016;Fitriyah 2012Fitriyah , 2015, Philippines (Hicken et al, 2019;Nowak & Snyder, 1974), Nigeria (Bratton 2008), and Africa (Lemarchand 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the records of the implementation of previous elections needs to find the best solution option. (Fitriyah, Laila Kholid Alfirdaus, 2021) Correction, analysis, and evaluation from the general election organizers who carried out their duties in previous elections and the people who directly participated in the elections must be formulated to strengthen the general election system that is increasingly qualified. The maturation process currently being carried out by the organizers of the general election with the government must present solution options that can minimize the risk of problems such as what happened in the 2019 general election (Retnowati, 2017).…”
Section: Introductionmentioning
confidence: 99%